Tooth Morphometry and Pattern of Palatal Rugae Among Monozygotic Twins in Malaysia - Widya Lestari; Nurliyana Afiqah Adanan; Nur Izzati Attiyah Mokhtar; Yunita Dewi Ardini; Solachuddin Jauhari Arief Ichwan; Muhammad Salahuddin Haris (Wolters Kluwer Medknow Publications, 2021)
Introduction: Monozygotic (MZ) twins share the same DNA, placenta, amniotic fluid, and physical features. Genetic factors play a prominent role compared to environmental factors in one's physical appearance, including dental morphology. Here we studied variation in MZ twin's tooth morphometry and palatal rugae pattern. Materials and methods: Variation between twins can be a valuable tool in forensics to identify individuals. Ten pairs of MZ twins were selected for this research. The maximum coronal mesiodistal and buccopalatal dimension of the maxillary teeth, excluding the second and third molars, were measured in triplicate using calipers. Palatal rugae patterns of the samples were cast, analyzed, and recorded based on shape and unification. Results: Our results showed a significant tooth dimension correlation between MZ twins. Maxillary central incisors had the least genetic variability, but the Carabelli trait, skeletal pattern, occlusion, and occlusal features all exhibited a greater correlation in MZ twins. Our findings provide compelling evidence for mirroring of dental features and palatal rugae patterns in MZ twins. This study is the first of its kind reported in Malaysia. Conclusion: Marked similarities in tooth morphometry and other dental physical features were observed between twins, which can be a useful tool in forensics for the identification of individuals.